AKTIVITAS ANTIBAKTERI DAUN PEPAYA (Carica Pepaya) MENGGUNAKAN PELARUT ETANOL TERHADAP BAKTERI Salmonella thypi - Sudarwati, Tri Puji Lestari (Journal of Research and Technology, 2018)
Typhoid fever is one of the health problems that often occur in people of Indonesia. The spreads of this desease are through contaminated food. Thyphoid fever could be caused by bacterials infection, one of the bactery is Salmonella typhi. One of solution o cure the infection is by using antibacterial derived from plants or herbs called traditional medicine.  This medicine is chosen and preffered because it has relatively small side effects. Carica papaya L. is the most kind of plant which is learnt for the function as antibacterial. This study aims to determine the concentration effects of papaya leaf extract to the inhibition zone of Salmonella typhi bacteria. The method to determine the concentration effect of papaya leaf extract is a paper disc difussion.  The results of this study at a concentration of 20 μg/ml, 40 μg/ml, 60 μg/ml, 80 μg/ml and 100 μg/ml indicate inhibiton zone in the category of moderate.